QURANIC SYNTACTIC STRUCTURES CLASSIFYING AND ANALYZING NA’T PATTERNS (MUFRAD, JUMLAH, SYIBH AL-JUMLAH) IN SŪRAH AL-WĀQI’AH - Virda Shofiah; Hafshoh Amatullah; Agung Pranoto Kadiatmaja (Universitas Islam Negeri Palopo, 2026)
This study aims to classify and analyze na’t (adjectival) patterns mufrad, jumlah, and syibh al-jumlah in Sūrah al-Wāqi’ah and to examine their functional roles in constructing eschatological meaning. Employing a qualitative descriptive-analytical approach on all 96 verses, data were analyzed using the Miles and Huberman interactive model with classification guided by al-Ghalyāyinī’s functional parameters distinguishing at-tawḍīḥ (clarification) in definite nouns from at-takhṣīṣ (specification) in indefinite nouns. The findings reveal that na’t mufrad predominantly encodes at-takhṣīṣ, conveying permanent properties (at-thubūt) that construct stable, sensory-rich images of paradise, while syibh al-jumlah functions as a spatial and temporal anchor situating eschatological realities within concrete dimensions. The dominant asymmetry of at-takhṣīṣ (37 of 43 entries) over at-tawḍīḥ (6 entries) reflects a coherent rhetorical strategy in which specification projects the desirability of paradise, while economy of description in punitive passages projects finality and inevitability. This study contributes a systematic syntactic-functional model applicable to Qur’anic linguistic analysis and offers a practical framework for advanced naḥwu instruction in Arabic language education.